1992
DOI: 10.1055/s-0038-1648448
|View full text |Cite
|
Sign up to set email alerts
|

The Glycosaminoglycan of Recombinant Human Soluble Thrombomodulin Affects Antithrombotic Activity in a Rat Model of Tissue Factor-Induced Disseminated Intravascular Coagulation

Abstract: SummaryPrevious studies on recombinant human soluble thrombomodulin (rsTM) from Chinese hamster ovary cells revealed that rsTM was expressed as two proteins that differed functionally in vitro due to the presence (rsTMp) or absence (rsTMa) of chondroitin-4-sulfate. The current study evaluates the in vivo behavior of rsTM in rats and in a rat model of tissue factor-induced disseminated intravascular coagulation (DIC). rsTMp was more potent than rsTMa for prolongation of the activated partial thromboplastin time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 4 publications
2
30
0
Order By: Relevance
“…The impact of thrombomodulin on the tail bleeding assay is in keeping with the results of several groups (40,41). Aoki demonstrated a prolongation of bleeding times using rhs-TBM, although the doses required were in excess of that needed to prevent tissue factor-induced disseminated intravascular coagulation in rats (41).…”
Section: Discussionsupporting
confidence: 84%
“…The impact of thrombomodulin on the tail bleeding assay is in keeping with the results of several groups (40,41). Aoki demonstrated a prolongation of bleeding times using rhs-TBM, although the doses required were in excess of that needed to prevent tissue factor-induced disseminated intravascular coagulation in rats (41).…”
Section: Discussionsupporting
confidence: 84%
“…The half-lives of ART-123 are relatively long compared with those of other thrombomodulin derivatives described previously. Nawa et al (38) demonstrated that recombinant human soluble thrombomodulin with glycosaminoglycan had a shorter half-life than that treated with chondroitinase AC I. The half-lives of thrombomodulin composed of the last three epidermal growth factor-like structures (E456) are very short in monkeys at 9 (t 1/2a ) and 50 min (t 1/2b ) (48).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…19 Further, systemic infusion of recombinant soluble THM has shown promise as a useful anticoagulant therapy. 20 Endothelial cells reflect the local pathophysiological milieu and play active roles in determining, among other processes, the procoagulant/anticoagulant balance. 21 A perturbed endothelial cell dramatically decreases expression of THM as a critical mechanism for shifting the local environment toward a procoagulant state.…”
mentioning
confidence: 99%